Physical fitness and neurocognitive outcomes in adult survivors of childhood acute lymphoblastic leukemia: A report from the St. Jude Lifetime cohort. Issue 3 (21st October 2019) - Phillips, Nicholas S.; Howell, Carrie R.; Lanctot, Jennifer Q.; Partin, Robyn E.; Pui, Ching‐Hon; Hudson, Melissa M.; Robison, Leslie L.; Krull, Kevin R.; Ness, Kirsten K.
Abstract : Background: Survivors of childhood acute lymphoblastic leukemia (ALL) are at increased risk for both treatment‐related exercise intolerance and neurocognitive deficits. This analysis aimed to identify the association between exercise intolerance and neurocognitive impairments in ALL survivors. Methods: Cardiopulmonary exercise testing, results from a 2‐hour standardized neuropsychological assessment, and self‐report questionnaires were obtained for 341 adult survivors of childhood ALL and 288 controls. Multivariable modeling was used to test associations between oxygen uptake at 85% estimated heart rate (rpkVO2 ) and neuropsychological test and self‐reported questionnaire domains, adjusted for sex, age at diagnosis, cranial radiation, anthracycline, and methotrexate exposure and tobacco smoking status. Results: Compared with controls, survivors had worse rpkVO2 and performance on verbal intelligence, focused attention, verbal fluency, working memory, dominant/nondominant motor speed, visual‐motor speed, memory span, and reading and math measures (all P < .001). In adjusted models, exercise intolerance was associated with decreases in performance of verbal ability, focused attention, verbal fluency, working memory, dominant motor speed, nondominant motor speed, visual‐motor speed, memory span, reading academics, and math academics in survivors. Conclusion: This study demonstrates an association between exercise intolerance and neurocognitive outcomes. Research is needed to determine whether interventions that improve exercise tolerance impact neurocognitive function in ALL survivors. Abstract : Previous studies in noncancer populations of children and older adults have shown that physical fitness interventions can have a positive impact on executive function and academic performance. The present study provides evidence that even with the neurotoxic effects of anticancer therapy, improving the physical fitness of pediatric cancer patients may have a similar long‐term impact on the neurocognitive outcomes of survivors.